Inverse problems with applications in science and engineering - Lesnic, D. (Daniel) (CRC Press, an imprint of the Taylor & Francis Group, 2022)
"Driven the advancement of industrial mathematics and the need for impact case studies, Inverse Problems with Applications in Science and Engineering thoroughly examines the state-of-the-art of some representative classes of inverse and ill-posed problems for partial differential equations (PDEs). The natural practical applications of this examination arise in heat transfer, electrostatics, porous media, acoustics, fluid and solid mechanics - all of which are addressed in this text. Features: Covers all types of PDEs, namely, elliptic (Laplace's, Helmholtz, modified Helmholtz, biharmonic, Stokes), parabolic (heat, convection-reaction-diffusion) and hyperbolic (wave) Excellent reference for post-graduates and researchers in mathematics, engineering, and any other scientific disciplines that deal with inverse problems Contains both theory and numerical algorithms for solving all types of inverse and ill-posed problems"--Provided by publisher.